2021
DOI: 10.48550/arxiv.2102.08446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoothed Analysis with Adaptive Adversaries

Abstract: We prove novel algorithmic guarantees for several online problems in the smoothed analysis model. In this model, at each time step an adversary chooses an input distribution with density function bounded above pointwise by 1 σ times that of the uniform distribution; nature then samples an input from this distribution. Crucially, our results hold for adaptive adversaries that can base their choice of an input distribution on the decisions of the algorithm and the realizations of the inputs in the previous time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 6 publications
0
30
0
Order By: Relevance
“…In this paper, we answer both questions. With regard to the first question, the natural extension of the covering-based argument in [HRS21] would yield suboptimal dependence on σ in the nonparametric regime; instead, we obtain a nonconstructive proof through careful application of combinatorial inequalities and an adaptation of the coupling lemma of [HRS20].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this paper, we answer both questions. With regard to the first question, the natural extension of the covering-based argument in [HRS21] would yield suboptimal dependence on σ in the nonparametric regime; instead, we obtain a nonconstructive proof through careful application of combinatorial inequalities and an adaptation of the coupling lemma of [HRS20].…”
Section: Introductionmentioning
confidence: 99%
“…Smoothed analysis in the setting of online learning was first introduced in [RST11], where the authors showed non-constructively that thresholds again become learnable in this setting. More recently, a series of papers [HRS20,HRS21] has demonstrated that the stochastic perturbation has beneficial effects in far greater generality than the class of thresholds; in fact, any classification task that is possible in the batch setting is also statistically tractable in the smoothed online setting.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations